Critical care emergency burn treatment - Cross, Pam; American Journal of Nursing Company (New York: American Journal of Nursing Company, 1995)
(Producer) Severe burns affect every major system of the body. Because the first steps of burn care are of vital importance and affect survival and quality of life after the burn, nurses must understand how to accurately assess, manage, and care for burn patients. This program demonstrates how to assess a patient on admission and explains the rationale for every action. Getting a complete history - how the burn occurred, type of burn, patient information - is stressed. The importance of a multi-system assessment throughout the initial period (usually 72 hours) is detailed. Other topics covered include: how the body reacts to burn trauma, the differences in emergency burn treatment for pediatric and adult patients, the initial steps in emergency care, and how to estimate the severity of the burn
Videocassettes are available at Koleksi Media Perpustakaan HUKM
Approved for 1 contact hr. of CE credit
Content expert, Pam Cross
Keywords: Burns -- nursing -- videocassettes; Critical Care -- videocassettes